PENGARUH PERCEIVED EASE OF USE DAN PERCEIVED USEFULNESS TERHADAP MINAT PENGGUNAAN QRIS PADA MERCHANT DI LOMBOK EPICENTRUM MALL - NURLAILA HIDAYATI; NINA KARINA KARIM (Universitas Mahasaraswati K. Mataram, 2024)
This study aims to determine the effect of perceived ease of use and perceived usefulness on interest in using QRIS on merchant at Lombok Epicentrum Mall. This study used an associative quantitative approach. This study used primary data taken from 131 respondents. The results showed that simultaneously the variables perceived ease of use and perceived usefulness had a positive and significant effect on the interest in using QRIS at merchants in Lombok Epicentrum Mal. Partially, the perceived ease of use variable and perceived usefulness has a positive and significant effect on the interest in using QRIS at merchants in Lombok Epicentrum Mall